2018
DOI: 10.1055/s-0038-1660779
|View full text |Cite
|
Sign up to set email alerts
|

Dementia and Hearing Loss: Interrelationships and Treatment Considerations

Abstract: Hearing loss is common among typically aging older adults and those with dementia. In recent years, there has been a renewed interest in the relationship between hearing and cognition among older adults, and in hearing loss as a modifiable risk factor for dementia. However, relatively less attention has been focused on the management of hearing loss among individuals with dementia and the key roles of speech-language pathologists and audiologists in providing such care. In this article, the authors review the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 77 publications
1
17
0
Order By: Relevance
“…Management of hearing loss and communication should be integrated into the person's broader dementia care [36] and delivered as close to the person's own setting as possible. Involving speech and language therapists working with audiologists can greatly increase opportunities for meaningful engagement in persons with dementia [39].…”
Section: Interventions For Hearing Loss In Dementiamentioning
confidence: 99%
See 1 more Smart Citation
“…Management of hearing loss and communication should be integrated into the person's broader dementia care [36] and delivered as close to the person's own setting as possible. Involving speech and language therapists working with audiologists can greatly increase opportunities for meaningful engagement in persons with dementia [39].…”
Section: Interventions For Hearing Loss In Dementiamentioning
confidence: 99%
“…Both hearing loss and dementia may cause social withdrawal and impairments in communication, functioning, participation in activities [39]. Among nursing home residents sensory impairments has been associated with low social engagement and low time spent in activities [45].…”
Section: Hearing Loss and Other Symptoms Of Dementiamentioning
confidence: 99%
“…Hearing impairment likely exacerbates the negative consequences of dementia on communication and quality of life for adults residing in RACFs (Hopper & Hinton, 2012;Hubbard, Mamo, & Hopper, 2018;Pichora-Fuller, Dupuis, Reed, & Lemke, 2013;Punch & Horstmanshof, 2018), yet, in research, this has been investigated sparingly. Cohen-Mansfield et al (2009) found that poorer hearing, as determined through a four-point scale where "1" represented those with highly impaired hearing and "4" represented those with adequate hearing, was associated with a higher refusal rate to engage in activities in 193 residents with dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, participants in the present study felt it was both important and beneficial to manage hearing impairment in residents living with dementia. dementia (Dawes et al, 2019;Hopper, 2007;Hubbard, Mamo, & Hopper, 2018;Mamo et al, 2018;Pichora-Fuller, Dupuis, Reed, & Lemke, 2013 (Conway & Chenery, 2016;Eggenberger, Heimerl, & Bennett, 2013;Sprangers, Dijkstra, & Romijn-Luijten, 2015) and for assisting adults with hearing impairment and their caregivers (Hickson, Worrall, & Scarinci, 2006 -Wendling, Pimple, Adams, & Titler, 2008;Cohen-Mansfield & Taylor, 2004a, 2004bCrosbie et al, 2019;Pryce, Hall, Laplante-Lévesque, & Clark, 2016;Slaughter et al, 2014). (Coulson, Ferguson, Henshaw, & Heffernan, 2016) to further explore this and other factors that influence hearing impairment management for people living with dementia who reside in RACFs.…”
Section: Themementioning
confidence: 99%
“…The co-occurrence of hearing impairment for adults living with dementia in RACFs has far-reaching consequences for individuals including affecting psychosocial behaviours (Bott, Meyer, Hickson, & Pachana, 2019b;Pryce & Gooberman-Hill, 2012), resident-caregiver communication (Bott, Meyer, Hickson, & Pachana, 2019b;Slaughter, Hopper, Ickert, & Erin, 2014), engagement and participation in social activities (Cohen-Mansfield, Marx, Regier, & Dakheel-Ali, 2009;Pryce & Gooberman-Hill, 2012), and causing increased functional difficulties (Guthrie et al, 2018). Thus, treating hearing impairment is considered important for improving the overall wellbeing of adults living with dementia who reside in RACFs (Hopper & Hinton, 2012;Hubbard, Mamo, & Hopper, 2018;Pichora-Fuller, Dupuis, Reed, & Lemke, 2013).…”
Section: Introductionmentioning
confidence: 99%